The Development Model of Woodball Kids Tools for Learning Physical Education in Elementary School - Said, Mohammad Ibnu; Rustiadi, Tri; Rahayu, Setya (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The objective of this study is to introduce woodball sports towards elementary school students with modified tools and test the effectiveness of woodball kids in the physical education and health science learning in the small ball games of elementary school. This research method used research and development. The results of the research are tools and models of woodball kids games as an introduction to woodball sports in elementary school. The effectiveness of the tool in use is validated by woodball tool experts of 93% and the sports education expert of 96% in the good category. Tools and games used 48 students of 90% in the good category. The conclusions of this study are an effective woodball kids model has been produced to introduce woodball sports in physical education learning in elementary school. The important finding that underlies the creation of this woodball kids tool is the development of a woodball game model combined with the physical education where the woodball kids game model in the learning process uses media such as the woodball kids tool developed in this study. It is suggested that this woodball kids tool can be used for all elementary school students because it has proven effective as a learning medium.